2004
DOI: 10.1007/s00299-003-0709-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of the flavonoid 3?,5?-hydroxylase gene of Vinca major alters flower color in transgenic Petunia hybrida

Abstract: Flavonoid 3',5'-hydroxylase (F3'5'H) is the key enzyme for the expression of blue or purple flower color. A full-length cDNA for the F3'5'H gene was cloned from petals of Vinca major, and its genomic clone, designated VmFH1 (accession number AB078781 in the GenBank/EMBL/DDBJ databases), was isolated from leaves by a PCR-based strategy. Nucleotide sequence analysis revealed that VmFH1 contains one intron and an open reading frame encoding a polypeptide of 506 amino acid residues. The deduced amino acid sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…These data are consistent with the anthocyanins accumulation pattern. In Vinca major anthocyanins were only detected in petals of stage 2-5 flowers with those of stage 4 flowers accumulating the largest amount of delphinidin (Mori et al 2004). These results suggested that Phf35h expression in the petals of Phalaenopsis is developmentally regulated and that anthocyanins accumulation may be under transcriptional control.…”
Section: The Expression Profiles Of Phalaenopsis F35h Genesmentioning
confidence: 96%
“…These data are consistent with the anthocyanins accumulation pattern. In Vinca major anthocyanins were only detected in petals of stage 2-5 flowers with those of stage 4 flowers accumulating the largest amount of delphinidin (Mori et al 2004). These results suggested that Phf35h expression in the petals of Phalaenopsis is developmentally regulated and that anthocyanins accumulation may be under transcriptional control.…”
Section: The Expression Profiles Of Phalaenopsis F35h Genesmentioning
confidence: 96%
“…After the first isolation and functional characterization of the genes encoding F3#H and F3#5#H in petunia (Petunia hybrida; Holton et al, 1993;Brugliera et al, 1999), the genes were subsequently isolated from various plant species. F3#H was characterized in Arabidopsis (Arabidopsis thaliana; Schoenbohm et al, 2000), and F3#5#H cDNAs were isolated from a number of plants, including Solanum melongena (Toguri et al, 1993), Gentiana triflora (Tanaka et al, 1996), Eustoma grandiflorum (Nielsen and Podivinsky, 1997), Eustoma rusellianum (Shimada et al, 1999), Catharanthus roseus (Kaltenbach et al, 1999), Campanula medium (Okinaka et al, 2003), and Vinca major (Mori et al, 2004). Some plants, including Arabidopsis and important members of the Rosaceae such as apples (Malus spp.)…”
mentioning
confidence: 99%
“…Genes encoding F3#H and F3#5#H have been isolated in myriad plant species, including petunia (Holton et al, 1993;Menting et al, 1994;Brugliera et al, 1999), Arabidopsis (Schoenbohm et al, 2000), lisianthus (Eustoma grandiflorum; Noda et al, 2004), and grape (Vitis vinifera; Bogs et al, 2006), among others. Manipulation of F3#H and F3#5#H genes has been effective in genetic engineering of floral crops to develop new genotypes with novel flower colors for ornamental purposes (Shimada et al, 1999;Mori et al, 2004;Nakatsuka et al, 2007).…”
mentioning
confidence: 99%